EFEK PENGGUNAAN SCR MOTOR CONTROLLER UNTUK PENINGKATAN EFISIENSI PADA MOTOR INDUKSI TIGA FASA - Rahman, Yuli Asmi; Nugraha, Deny Wiria (MEKTEK, 2006)
AC Induction motors are sized for maximum load and are operated at a constant full speed, because they are supplied with power from AC lined at a fixed-sinusoidal voltage and fixed frequency. However, load of motor does not always same at many conditions but the input voltage and power of motor is fixed. Of course, it will influence the efficiency of the motor. One method to improve efficiency of the motor is varying the voltage as loaded its and called Motor Controlled. Motor Controlled is AC Drive that using SCR (Silicon Controlled Rectifier) as the output voltage controller by controlling the firing angle. By employing SCR Motor Controller that adjust the voltage of the motor offers advantageous to improve efficiency of motor and potential for significant energy savings.